Peran Filsafat dalam Memahami Transformasi Sosial dan Budaya - Ummu Mutia Pasaribu; Fitri Lannora Nst; Dania Nasution; Rezki Khairani Hasibuan; Anggina Safitri; Dini Khairani Hasibuan; Anita Sari Daulay; Alwi Sahaf Lubis; Nurhayati Siregar (KAMPUS AKADEMIK PUBLISING, 2026)
The demographic bonus represents a strategic opportunity for Indonesia to accelerate national development toward the Indonesia Golden Vision 2045. However, its successful realization largely depends on the quality of substantive democracy. This study aims to analyze the relationship between the demographic bonus and substantive democracy and their implications for national development. The research employs a qualitative approach using a library research method. Data were collected from government documents, reports of international organizations, books, and peer-reviewed scientific journals, and were analyzed through content analysis involving literature selection, interpretation, and critical synthesis. The findings indicate that the demographic bonus cannot be optimally transformed into sustainable development without democratic, transparent, accountable, and participatory governance. Democratic backsliding, characterized by weakened civil institutions, declining public participation, and the strengthening of oligarchic practices, may hinder human capital development, employment opportunities, and inclusive economic growth. Therefore, strengthening substantive democracy is essential as a prerequisite for maximizing the demographic bonus and achieving sustainable national development toward Indonesia Golden Vision 2045.